Auditory filters in sensorineural hearing impaired subjects - Skrodzka, E. B.; Wicher, A.; Ozimek, E.; Sęk, A. P. (Archives of Acoustics, 2002)
The study is devoted to determination of the shape of the auditory filters in subjects with sensorineural hearing loss. Apart from the classical sensorineural hearing loss, changes in the auditory filter shapes have been analysed in the subject diagnosed with dead regions. The dead region is an area on the basilar membrane over which the functioning of the inner hair cells and/or neurones innervating them has ceased. This type of hearing impairment means that the information on the sounds whose frequencies correspond to the dead region of the basilar membrane are to a very limited degree if at all, transmitted to higher levels of the auditory path. This transmission, if happens, is performed through the auditory filters at the centre frequency other than that of the signal. This phenomenon and the fact that in the dead region the hearing loss is theoretically infinite, affect the transmittance of the auditory filters. Results of the study reported here have shown that in general, the subjects with sensorineural hearing loss develop broadening of the auditory filter accompanied by reducing of its dynamics. This fact explains a considerable decrease in speech intelligibility presented at a background of a noise. In the subject with the dead regions the broadening of the filters was the greatest in the region of the dead one. The results also indicate the lack of correlation between the shape and width of the auditory filter and the shape of the audiogram.